VAC Therapy as Part of Complex Treatment of Deep Sternal Wound Infection in Cardiosurgical Patients: First Experience - Osaulenko, Vyacheslav V.; Chmul, Karina O.; Budagov, Rasim I. (Ukrainian Journal of Cardiovascular Surgery, 2023)
The aim. To improve the immediate and long-term results of treatment of cardiac surgery patients, by determining the feasibility of using wound therapy with negative pressure (vacuum assisted closure [VAC] therapy) as part of the complex tactics of postoperative management of patients with deep sternal wound infection (DSWI). Materials and methods. A single-center, retrospective, observational study of the clinical data of 12 patients who underwent open-heart surgery using median sternotomy and who developed a DSWI was conducted. The mean age of the patients was 66.2 ± 2.2 years. The patients were divided into 2 groups, depending on the type of the treatment they received: group 1 included 5 (41.67%) subjects with the installation of a flow-washing system; group 2 included 7 (58.33%) subjects receiving negative pressure wound therapy. Results. The use of VAC therapy contributed to the reduction of all indicators characterizing the course of the wound process, compared to patients treated with traditional methods. The duration of hospitalization was 36.2 ± 3.3 days in group 1 and 42 ± 4.0 days in group 2. The level of in-hospital mortality in the studied group receiving negative pressure wound therapy was 14.29% (1 patient) versus 80% (4 patients) in the group with flow-irrigation drainage. Conclusions. Deep sternal wound infection is a very serious postoperative complication in cardiac surgical patients with a high in-hospital mortality rate. Diabetes mellitus, obesity, immunopathies are the main risk factors. VAC therapy in patients with DSWI allows to adequately repair the wound in a shorter time while maintaining the patient’s mobility, as well as to significantly reduce the duration of wound drainage and, as a result, the length of hospitalization.